Evaluación de la estrategia: línea de atención psicológica telefónica y presencial, ofrecida por Médicos sin Fronteras, en habitantes de Buenaventura, Colombia, entre 2016 y 2019 (2021)
Objective. Evaluate the results of the psychological care line, offered by Médecins Sans Frontir¿es in the population of Buenaventura, Colombia, during the period 2016-2019. Methods. Descriptive study, with a retrospective orientation, based on three secondary sources of Médecins Sans Frontir¿es that had a record of information of the people attended by the psychological care line by telephone, face-to-face or mixed. It is divided into two periods: from January 2016 to June 2018, in which an analogous Visual Scale was used to measure symptom intensity and function impairment, with a total of 1596 observations; and from July 2018 to December 2019, in which it was used the Global Clinical Impression and Mental Health Results scales with a total of 1062 data. Measures of central tendency were used for quantitative variables and frequency for qualitative variables. In addition, the differences in the scores of the scales between the first and last session...